HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN DETEKSI DINI CA CERVIKS MELALUI METODE IVA DI KELURAHAN ARO IV KORONG WILAYAH KERJA PUSKESMAS KTK KOTA SOLOK - Armanda Tri Murti Ningsih (Ensiklopedia of Journal, 2019)
IVA (Visual Inspection with Acetic Acid) is one way to do a cervical cancer test. If the results of the mother's IVA examination are positive (the presence of precancerous lesions), it can be treated immediately. If not, then the virus can spread and develop into cancer. This research design uses a research method of correlation studies with a cross sectional approach. The population of this study was all mothers of childbearing age with a sample of 36 people. The results showed that more than half (52.8%) of respondents had high knowledge, more than half (55.6%) of respondents had a positive attitude and more than half (66.7%) of respondents did not detect early Ca cervix, there were significant relationship between knowledge level p = 0.001, attitude p = 0.004 with early Ca Cerviks.The need to provide counseling in Posyandu or meeting places for mothers in the area and increase socialization activities for the community about the importance of IVA examinations in the form of health media such as TV, radio, or leaflets so that they have knowledge about the risk of Ca cervix and are willing to carry out IVA examinations.